Development of Islamic Value-Based Career Guidance Modules and Interactive Multimedia to Improve Students' Career Maturity - Efendi, Moh. Yusuf; Distira, Riski Putra Ayu (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to develop a career guidance module integrated with Islamic values and interactive multimedia to enhance students' career maturity. The research uses qualitative and quantitative data to follow the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. Quantitative data focuses on measuring students' career maturity before and after module implementation, while qualitative data is collected from expert evaluations and interviews with teachers and students. The sampling technique used is purposive sampling, involving vocational high school students and teachers in Bojonegoro. Data collection methods include interviews, expert questionnaires, and field trials. The results show that the module improves students' motivation, self-confidence, and awareness of career preparation. Islamic values embedded in the module also help students develop ethical and moral principles in their future work lives. Interactive media, such as simulations, videos, and animations, increase student engagement and understanding. However, the study is limited by its focus on vocational schools in Bojonegoro and the short duration of the field trials. Future research should expand the sample size and trial period to assess long-term effects better. Field trials significantly increased students' career maturity after using the module.